Learning faster or more precisely? Strategic experimentation in networks - Mirjam Wuggenig (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
The paper analyzes a dynamic model of rational strategic learning in a network. It complements existing literature by providing a detailed picture of short-run dynamics in a game of strategic experimentation where agents are located in a social network. We show that the delay in information transmission caused by incomplete network structures may induce players to increase own experimentation efforts. As a consequence a complete network can fail to be optimal even if there are no costs for links. This means that in the design of networks there exists a trade-off between the speed of learning and accuracy.
Keywords: C73; D83; D85; 330